High prevalence of patent foramen ovale in recreational to elite breath hold divers. Issue 7 (July 2022) - Kelly, Tyler; Patrician, Alexander; Bryant-Ekstrand, Mohini; Brown, Courtney; Gasho, Christopher; Caldwell, Hannah G.; Lord, Rachel N.; Dawkins, Tony; Drane, Aimee; Stembridge, Michael; Dragun, Tanja; Barak, Otto; et al.
Abstract: Objectives: During apnea diving, a patent foramen ovale may function as a pressure relief valve under conditions of high pulmonary pressure, preserving left-ventricular output. Patent foramen ovale prevalence in apneic divers has not been previously reported. We aimed to determine the prevalence of patent foramen ovale in apneic divers compared to non-divers. Design: Cross sectional. Methods: Apnea divers were recruited from a training camp in Cavtat, Croatia and the diving community of Split, Croatia. Controls were recruited from the population of Split, Croatia and Eugene, Oregon, USA. Participants were instrumented with an intravenous catheter and underwent patent foramen ovale screening utilizing transthoracic saline contrast echocardiography. Appearance of microbubbles in the left heart within 3 cardiac cycles indicated the presence of patent foramen ovale. Lung function was measured with spirometry. Comparison of patent foramen ovale prevalence was conducted using chi-square analysis, p < .05. Results: Apnea divers had a significantly higher prevalence of patent foramen ovale (19 of 36, 53%) compared to controls (9 of 36, 25%) ( X 2 (1, N = 72) = 5.844, p = .0156). Conclusions: Why patent foramen ovale prevalence is greater in apnea divers remains unknown, though hyperbaria during an apnea dive results in a translocation of blood volume centrally with a concomitant reduction in lung volume and alveolar hypoxia during ascent results in hypoxic pulmonary vasoconstriction. These conditions increase pulmonary arterial pressure, increasing right-atrial pressure allowing for right-to-left blood flow through a patent foramen ovale which may be beneficial for preserving cardiac output and reducing capillary hydrostatic forces.